Single Balloon Enteroscopy-assisted Balloon Dilation of Roux-en-Y Jejunojejunostomy Stricture - Palakurthy, Murali Krishna; Girinadh, L.R.S.; Uppala, Bhaskar Rao; Korrapati, Sravan Kumar (Journal of Digestive Endoscopy, 2017)
Total gastrectomy with Roux-en-Y esophagojejunostomy is a procedure commonly performed for gastric cancer patients. Postoperative stricture at esophagojejunostomy site is commonly reported, but a stricture at jejunojejunostomy site is rarely reported. We report a rare case of stricture at Roux-en-Y jejunojejunostomy site which was managed successfully by endoscopic intervention.
Keywords: Enteroscopy; Roux-en-Y jejunojejunostomy; stricture